Political commitment and transparency as a critical factor to achieve territorial cohesion and sustainable growth. European cross‐border projects and strategies. Issue 2 (16th May 2019) - Castanho, Rui Alexandre; Vulevic, Ana; Naranjo Gómez, José Manuel; Cabezas, José; Fernández‐Pozo, Luis; Loures, Luís; Kurowska‐Pysz, Joanna
Abstract: Political commitment and transparency have been previously identified as critical factors for territorial success, as well as factors which allow the achievement of stronger cohesion and sustainable growth of cross‐border cooperation projects and strategies. The present study is aimed at a more thorough analysis of these factors. Throughout the analysis and assessment of the European CBC case studies, where political commitment has been defined as a critical factor, political and economic transparency plays a key role. This analysis, which incorporates public and technical opinions, provides a better comprehension on how these factors influence the European panorama. It includes the key messages for policy‐makers when designing and implementing development strategies specifically tailored to the needs of these places.